2018
DOI: 10.22159/ajpcr.2018.v11i1.22588
|View full text |Cite
|
Sign up to set email alerts
|

Valeriana Officinalis: A Review of Its Traditional Uses, Phytochemistry and Pharmacology

Abstract: Valeriana is a well-known Indian traditional medicinal herb with sleep remedy. It has been used over the years to treat nervine and sedative in hysteria, epilepsy, and sedative in nervous anxiety. It has also been used as an aromatic stimulant and reported some distinctive indications, as well as its use for rheumatism, low-grade fevers, and aphrodisiac. It has been known to grow well in regions of Europe, parts of Asia and North America. This systematic review focuses on the ethnopharmacological uses of Valer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(10 citation statements)
references
References 36 publications
(49 reference statements)
0
7
0
3
Order By: Relevance
“…The plant is native to Asia, Europe, and North America and is included in at least 20 pharmacopeias worldwide. Valerian contains a sesquiterpenoid, valerenic acid as the main constituent [46]. In Traditional medicine, the plant has been used in spasms, cardiac arrhythmias, insomnia, hysteria, hypochondriasis, emotional states, convulsions, digestive problems, and urinary tract infections [46,47].…”
Section: Valeriana Officinalis Lmentioning
confidence: 99%
“…The plant is native to Asia, Europe, and North America and is included in at least 20 pharmacopeias worldwide. Valerian contains a sesquiterpenoid, valerenic acid as the main constituent [46]. In Traditional medicine, the plant has been used in spasms, cardiac arrhythmias, insomnia, hysteria, hypochondriasis, emotional states, convulsions, digestive problems, and urinary tract infections [46,47].…”
Section: Valeriana Officinalis Lmentioning
confidence: 99%
“…960 species) has a worldwide distribution range [1], but only a few species are used as medicinal plants. These include, e.g., Valeriana officinalis, which is traditionally used for the treatment of insomnia, mild nervous conditions, and menopausal symptoms and is recommended for the treatment of gastrointestinal pain and spastic colitis [2,3], Lonicera caprifolium with its diuretic, diaphoretic, and antibacterial effects, and L. japonica, used for the treatment of prostatitis and hypertension [2]. It should be emphasized that many Caprifoliaceae species have not yet been analyzed for the presence of high contents of secondary metabolites and their broad-sense medicinal use.…”
Section: Introductionmentioning
confidence: 99%
“…(Vj) and Nardostachys jatamansi (D.Don) DC. (Nj) [12][13][14]. The roots of Vo and Nj, because of high commerce, are often fraudulently adulterated with other species [15].…”
Section: Introductionmentioning
confidence: 99%
“…Vo is a perennial herb common in North America, Europe, and Asia. Its rhizome is short and stoloniferous, and the roots are fibrous and have a characteristic smell [12]. Studies on Vo root extract have revealed many chemical compounds with a broad spectrum of biological activities on the CNS such as sesquiterpenes (valerenic acid and derivatives) and valepotriates, flavonoids, triterpenes, lignans, alkaloids, amino acids such as c-aminobutyric acid and Îłaminobutyric acid (GABA) as well as quinolinic acid with antioxidant and lipid peroxidation-decreasing effects [12,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation